An Introductory Study of Some selected Islamic Encyclopaedias compiled in Turkish Era: عصر ترکی میں مدون شدہ منتخب اسلامی موسوعات کا تعارفی مطالعہ - Sadna Zeb, sadna (AL-IDRAK JOURNAL, 2021)
The whole Islamic history can be divided into five different eras among which the fourth era is called the Turkish Era (656-1798 AD). As Islam has its own rich history due to its contribution to almost every aspect of human life, but the compilation of knowledge with its multiplicities has its own distinguished status. Although the Turkish era is called ''the age of decline of knowledge'' but it has been repudiated because a large number of books have been added to the series of world libraries in various fields/subjects. To evaluate the addition in to the specific area i.e. encyclopaedia writing, the current study is an attempt to make the reader know about the rich and diversified knowledge, disseminated in this era. Many books have been written down and researches are conducted in this field of study but there is lack of knowledge about this area for Urdu speakers. For this purpose, this study has an introductory sketch about the famous encyclopaedias written during the Turkish era. Adding more, the second purpose of this research is to investigate that why the Turkish era is being labelled as the era of decline of knowledge. The present research has used descriptive method, which is basically divided into three parts. First part is about the introduction and history of encyclopaedia, its status in the beginning of Islamic era. The second part contains a detailed study of Islamic encyclopaedias in Turkish era, and the famous writers. At the end, the article deals with the results of the study.